(3x-10)+(x+40)=65

Simple and best practice solution for (3x-10)+(x+40)=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-10)+(x+40)=65 equation:


Simplifying
(3x + -10) + (x + 40) = 65

Reorder the terms:
(-10 + 3x) + (x + 40) = 65

Remove parenthesis around (-10 + 3x)
-10 + 3x + (x + 40) = 65

Reorder the terms:
-10 + 3x + (40 + x) = 65

Remove parenthesis around (40 + x)
-10 + 3x + 40 + x = 65

Reorder the terms:
-10 + 40 + 3x + x = 65

Combine like terms: -10 + 40 = 30
30 + 3x + x = 65

Combine like terms: 3x + x = 4x
30 + 4x = 65

Solving
30 + 4x = 65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 4x = 65 + -30

Combine like terms: 30 + -30 = 0
0 + 4x = 65 + -30
4x = 65 + -30

Combine like terms: 65 + -30 = 35
4x = 35

Divide each side by '4'.
x = 8.75

Simplifying
x = 8.75

See similar equations:

| 150m+100m+48000=51000+200m | | -4a+6+6a=9a-5a | | 8=-12k/-4 | | -5.2M+11.51=-3.41 | | 19-37=-6x | | -4a+6+6a=9a-5 | | 5x+1+6x=11 | | -5x^2-3x+1=0 | | -20y+8=8y-4 | | 27.3m-45.1=-13.2+6.8m | | 3(5a-2)-2(3-2a)+a-3=0 | | 9x-1+3(4-4x)=0 | | 7x+2x=8x-1 | | -5.2M+11015=-3041 | | 3x+16=4x+13 | | 4t-t-7=2t-8 | | 15x+40=-88 | | 6x+x-8=6x+4 | | .56-0.32=1.12 | | 4x+32=8x+4 | | 4.3y=-3.44 | | 4/9=h/24 | | 2x+4x=26 | | 1/6X-17.1=-18 | | 4x+9x-63=84-8x | | 4(8-c)=8c+16-6c | | 28=(x-.5)+9 | | 28x+12y=8 | | 8y/6+3/6=5y/6 | | -39+8m=-5(1-5m) | | 10-9v+v= | | 5+3(2x-4)=9-4+(3x+1) |

Equations solver categories